Association and expression of the antigen‐processing gene PSMB8, coding for low‐molecular‐mass protease 7, with vitiligo in North India: case–control study. (1st February 2018) - Dani, P.; Patnaik, N.; Singh, A.; Jaiswal, A.; Agrawal, B.; Kumar, A.A.; Varkhande, S.R.; Sharma, A.; Vaish, U.; Ghosh, P.; Sharma, V.K.; Sharma, P.; et al.
Summary: Background: Vitiligo is a multifactorial, autoimmune, depigmenting disorder of the skin where aberrant presentation of autoantigens may have a role. Objectives: To study the association of two antigen‐processing genes, PSMB8 and PSMB9, with vitiligo. Methods: In total 1320 cases of vitiligo (1050 generalized and 270 localized) and 752 healthy controls were studied for the PSMB9 exon 3 G/A single‐nucleotide polymorphism (SNP), PSMB8 exon 2 C/A SNP and PSMB8 intron 6 G/T SNP at site 37 360 using polymerase chain reaction (PCR)–restriction fragment length polymorphism. Real‐time PCR was used for transcriptional expression of PSMB8 and cytokines. Expression of ubiquitinated proteins and phosphorylated‐p38 (P‐p38) was studied by Western blotting. Results: Significant increases in PSMB8 exon 2 allele A ( P < 2.07 × 10 −6, odds ratio 1·93) and genotypes AA ( P < 1.03 × 10 −6, odds ratio 2·51) and AC ( P < 1.29 × 10 −6, odds ratio 1·63) were observed in patients with vitiligo. Interferon‐γ stimulation induced lower expression of PSMB8 in peripheral blood mononuclear cells of cases compared with controls, suggesting impaired antigen processing, which was confirmed by accumulation of ubiquitinated proteins in both lesional and nonlesional skin of patients with vitiligo. Expression of proinflammatory cytokines – interleukin (IL)‐6, IL‐1β and IL‐8 – was higher in the lesional skin. P‐p38 expression was variable but correlated with the amount of ubiquitinated proteins in the lesional and nonlesional skin, suggesting that the inflammatory cytokine responses in lesional skin could be a result of both P‐p38‐dependent and ‐independent pathways. Conclusions: The PSMB8 exon 2 SNP is significantly associated with vitiligo. Accumulation of ubiquitinated proteins in skin of cases of vitiligo suggests their aberrant processing, which may promote the development of the disease.